A BIM-based Framework for Building Depreciation Estimation through Maintenance Management Integration - P. Jafary; P. Jafary; D. Shojaei; A. Rajabifard; T. Ngo; T. Ngo (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper proposes a framework for dynamic depreciation estimation by integrating Building Information Modelling (BIM), cost estimation datasets and maintenance data from Computerized Maintenance Management Systems (CMMS) or Facility Management Systems (FMS). The framework operates within a Common Data Environment (CDE), a centralized platform that consolidates and synchronizes data across various systems. By leveraging interoperability standards such as Industry Foundation Classes (IFC) and Construction-Operations Building Information Exchange (COBie), the framework facilitates seamless data exchange and integration. Maintenance records, asset conditions, lifecycle data and costs of building work items are systematically tracked within the CDE, enabling real-time updates and comprehensive visibility into the state of building components. This integration provides a robust foundation for accurate and condition-based depreciation estimation, enhancing property valuation practices by reflecting the actual wear, usage and maintenance history of building assets.